HUTAN MANGROVE SEBAGAI PELINDUNG GARIS PANTAI DAN PINTU MASA DEPAN EKOWISATA: HUTAN MANGROVE SEBAGAI PELINDUNG GARIS PANTAI DAN PINTU MASA DEPAN EKOWISATA - Yohanes Basuki Dwisusanto; Bachtiar Fauzy; Samantha Theresia (Universitas Telkom, 2025)
Abstract : As an archipelago with an extremely long coastline, Indonesia is highly vulnerable to coastal erosion and climate-related disasters. Approximately 29% of Indonesia’s coastline is experiencing erosion of varying severity; one nature-based solution that has proven effective in mitigating these impacts is mangrove forests. Mangrove forests are coastal ecosystems that play a vital role in protecting shorelines from abrasion and maintaining biodiversity, while also contributing to climate change mitigation through carbon sequestration. This study aims to examine the role of mangroves as natural coastal barriers and their potential as the foundation for sustainable ecotourism development. The method used is a literature review, analyzing scientific publications, environmental institutional reports, and government policies related to mangroves and ecotourism. The findings indicate that mangroves effectively reduce the impact of sea waves and tsunamis and provide natural habitats for diverse flora and fauna. Furthermore, mangrove ecotourism can offer economic benefits to local communities if managed sustainably and with active community participation. Integrated and inclusive management involving all stakeholders is essential to preserving the ecosystem while improving the welfare of coastal communities. These findings affirm that mangrove ecotourism development can be a strategic solution combining environmental conservation with economic empowerment in coastal areas. Keywords : mangrove forest; coastline; ecotourism; conservation; literature review